Beaker people in Britain: migration, mobility and diet. (17th May 2016) - Parker Pearson, Mike; Chamberlain, Andrew; Jay, Mandy; Richards, Mike; Sheridan, Alison; Curtis, Neil; Evans, Jane; Gibson, Alex; Hutchison, Margaret; Mahoney, Patrick; Marshall, Peter; Montgomery, Janet; et al.
Abstract: Abstract : The appearance of the distinctive 'Beaker package' marks an important horizon in British prehistory, but was it associated with immigrants to Britain or with indigenous converts? Analysis of the skeletal remains of 264 individuals from the British Chalcolithic–Early Bronze Age is revealing new information about the diet, migration and mobility of those buried with Beaker pottery and related material. Results indicate a considerable degree of mobility between childhood and death, but mostly within Britain rather than from Europe. Both migration and emulation appear to have had an important role in the adoption and spread of the Beaker package.